The relationship between willingness to pay, attitude and health knowledge with intention of consuming organic food among working women in Kelantan - Md Jusoh, Zuroni; Mohamad Zailani, Siti Faaiqah (Malaysia Consumer and Family Economy Association, 2021)
The research aimed to determine the relationship between willingness to pay (WTP) organic food products, attitudes of women in purchasing organic food products and health knowledge in buying organic food products with the intention of consuming organic food. A survey had been done amongst 253 working women in Kota Bharu, Kelantan, via purposive random sampling method. A self-administered bilingual questionnaire was used to collect the research data among respondents to examine their intention of consuming organic food. Pearson Correlation test was used to study the relationship between the independent variables and the dependent variable. The findings showed a significant relationship between WTP organic food products and intention to purchase organic food (r = 0.781**, p = 0.001). Also, there was a significant relationship between attitudes of women in the purchase of organic food products and intention to purchase organic food (r = 0.565**, p = 0.001) and a significant relationship between health knowledge in buying organic food products and intention to purchase organic food (r = 0.776**, p = 0.001). In conclusion, all the variables were a significant relationship. Therefore, the sellers need to create something new about organic packaging. The more people know about organic products, the more they can believe the organic products claim. People who know more about eco-friendly advertising are more willing to purchase organic food products.